'Reading landscape': interdisciplinary approaches to understanding place. Issue 3 (20th November 2019) - Smith, M. J.; Parrott, F.; Monkman, A.; O'Connor, J.; Rousham, L.
ABSTRACT: This paper outlines a collaborative project between a group of Fine Art and Geography students who helped develop and contribute to a conversation about recording 'place'. Introducing methodologies from both disciplines, the project started from the premise of all environmental 'recordings' being 'inputs' and so questioned what could be defined as 'data' when encountering a location. Brunel's Grand Entrance to the Thames Tunnel (London) provided the motivation for 10 objective and subjective 'recordings' which were subsequently distilled into a smaller subset and then used to produce a short film that was presented at an international conference. Important to the collaborative nature of the project were ongoing opportunities to share equipment, techniques, material and references across disciplines. It was an experiment to measure the potential for 'mapping' to capture physical and historical information, as well as embodied experience.